An exploration of predictors of children's nurses' attitudes, knowledge, confidence and clinical behavioural intentions towards children and young people who self‐harm. Issue 13 (19th April 2018) - Carter, Tim; Latif, Asam; Callaghan, Patrick; Manning, Joseph C.
Abstract : Aims and objectives: To explore the potential predictors of children's nurses' attitudes, knowledge and confidence towards caring for children and young people admitted to hospital with self‐harm. Background: Admissions to paediatric inpatient settings for individuals who have self‐harmed are growing. Limited previous research suggests that nurses have mixed attitudes towards people who have self‐harmed and potentially lack the confidence to provide effective care. There is a specific paucity of research in this area for children's nurses. Design: A cross‐sectional descriptive survey was used to gather data for exploration of variables associated with attitudes, confidence, knowledge and clinical behavioural intentions of 98 registered children's nurses in a single tertiary children's hospital, colocated in a large acute NHS Trust in the UK. Methods: Data were collected over a 4 weeks in 2015, using an online survey tool. The predictive effect of several demographic variables was tested on the outcomes of attitudes, knowledge, confidence and behavioural intentions, which were collected using relevant, previously used outcome measures. Results: Increased experience was found to be associated with improved attitudes relating to negativity. Previous training in caring for children who had self‐harmed was found to be associated with improved attitudes around perceived effectiveness of their care. Higher academic qualifications and having undertaken previous training on self‐harm were each found to be associated with increased knowledge of self‐harm, and increased age was associated with reduced knowledge of self‐harm. Conclusions: This study provides an initial exploration of variables associated with attitudes, knowledge, confidence and behaviour intentions of registered children's nurses in relation to caring for CYP who have self‐harmed. Relevance to clinical practice: Targeted training on caring for CYP who have self‐harmed should be considered as a component of continuing education for registered children's nurses in the UK to improve the experience and outcomes for this patient group.